2010
DOI: 10.1186/cc8916
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of dexmedetomidine versus lorazepam on outcome in patients with sepsis: an a priori-designed analysis of the MENDS randomized controlled trial

Abstract: IntroductionBenzodiazepines and α2 adrenoceptor agonists exert opposing effects on innate immunity and mortality in animal models of infection. We hypothesized that sedation with dexmedetomidine (an α2 adrenoceptor agonist), as compared with lorazepam (a benzodiazepine), would provide greater improvements in clinical outcomes among septic patients than among non-septic patients.MethodsIn this a priori-determined subgroup analysis of septic vs non-septic patients from the MENDS double-blind randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
286
2
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(305 citation statements)
references
References 64 publications
(100 reference statements)
7
286
2
10
Order By: Relevance
“…Especially benzodiazepines (act through γ-aminobutyric acid, GABA A receptors) pose great risk for developing delirium.They have been associated with delirium in several studies across multiple ICU populations. Three randomized trials (MENDS, SEDCOM and Maldonado´s study) comparing benzodiazepines to an alternative sedative (dexmedetomidine) demonstrate significantly lower prevalence of delirium, more days alive and days free of delirium or coma with dexmedetomidine [43][44][45] . It is time to change the practise of sedation.…”
Section: Drug-induced Sedationmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially benzodiazepines (act through γ-aminobutyric acid, GABA A receptors) pose great risk for developing delirium.They have been associated with delirium in several studies across multiple ICU populations. Three randomized trials (MENDS, SEDCOM and Maldonado´s study) comparing benzodiazepines to an alternative sedative (dexmedetomidine) demonstrate significantly lower prevalence of delirium, more days alive and days free of delirium or coma with dexmedetomidine [43][44][45] . It is time to change the practise of sedation.…”
Section: Drug-induced Sedationmentioning
confidence: 99%
“…Others are modifiable, such as minimizing the drug-induced sedation and the duration of artificial ventilation. The use of sedation may disturb neurotransmission in the brain (the use of benzodiazepines, propofol, or morphine) and was shown to be a risk factor in previous studies 16,21,[41][42][43] . Especially benzodiazepines (act through γ-aminobutyric acid, GABA A receptors) pose great risk for developing delirium.They have been associated with delirium in several studies across multiple ICU populations.…”
Section: Drug-induced Sedationmentioning
confidence: 99%
“…Sedation with dexmedetomidine resulted in more days alive without delirium or coma (p00.01) and lower prevalence of coma (p<0.001) than sedation with lorazepam. A subgroup analysis of the database from the study, which was planned a priori, demonstrated that sedation with dexmedetomidine reduced the daily risk of delirium as well (p00.02) [132] (Fig. 1a), and this effect was most prominent in patients with severe sepsis.…”
Section: Dexmedetomidine and Deliriummentioning
confidence: 97%
“…Note that both groups start with 60% prevalence of delirium in keeping with most cohorts of mechanically ventilated patients, and then there is a large difference in delirium prevalence throughout the remainder of the study period. Adapted from Pandharipande, et al [132]. (b) In the Safety and Efficacy of Dexmedetomidine Compared with Midazolam (SEDCOM) trial comparing dexmedetomidine to midazolam for sedation of mechanically ventilated patients, the prevalence of delirium in dexmedetomidine-treated patients was significantly less than midazolam-treated patients (54% vs 76.6%; p<0.001).…”
Section: Dexmedetomidine and Deliriummentioning
confidence: 99%
“…Predisposing and precipitating risk factors for the development of delirium in the elderly in ICU , sleep disturbances 5,9,12,19 , invasive devices 9,13 and environmental characteristics of the ICU as artificial lighting, noise, family isolation. 7,9 The delirium association with the aggravation of chronic Comorbidities that culminate with hepatic dysfunction, cardiovascular and renal has been described in five studies.…”
mentioning
confidence: 99%